Prevalence of Smoking and Associated Sociodemographic Factors in Older Adults in Primary Health Care. - Silva de Jesus, Ana Clara (2025)
Introduction: The increase in the older adult population, while positive, poses challenges related to chronic diseases, including smoking, which remains understudied. Objective: To estimate the prevalence of smoking among older adults and assess its association with sociodemographic factors. Methods: A cross-sectional study was conducted with 1,322 older adults receiving primary healthcare services across the state of Roraima, Brazil. Tobacco use was assessed by healthcare professionals. The available sociodemographic variables included sex, age, skin color, education level, and place of residence. Logistic regression was used to calculate Odds Ratios (OR) for possible associations. Results: The prevalence of smoking was 11.6% and showed significant differences across sociodemographic groups (p < 0.05), except for the education level (p = 0.06). Smoking among older adults was directly associated with the male sex (OR = 1.77), the 60–69 age group (OR = 4.70), and the indigenous (OR = 2.97) and yellow (OR = 2.54) skin colors, while it was inversely associated with higher education (OR = 0.44). The place of residence was not significant after adjustment. Conclusion: With one in ten older adults smoking, this study highlights the need for public policies aimed at smoking prevention, particularly among men, younger older adults, indigenous individuals, and those with lower education levels. Smoking cessation programs targeting specific groups can help reduce chronic diseases, improve the quality of life of older adults, and alleviate the burden on healthcare systems.